S12 The changes in incidence and management of pleural empyema in England over the last decade. (12th November 2019) - Arnold, DT; Hamilton, FW; Morris, TT; Payne, R; Maskell, NA
Abstract : Introduction: Pleural empyema represents a significant healthcare burden due to extended hospital admissions and/or requirement for surgical intervention. Epidemiological studies from Europe and North America have shown a steady increase in incidence, especially in the elderly. 1 2 No epidemiological studies have been performed in England. This study aimed to assess changes in incidence and management of pleural empyema over the last 10 years. Methods: Hospital Episode Statistics data was used to identify every patient admitted to an English hospital with pleural empyema (code J86), as well as all previously validated codes for viral influenza and pneumonia. Descriptive statistics were used to represent the change in empyema incidence, management and mortality. Linear regression analysis was used to compare the incidence of empyema with other respiratory infections. Results: Between April 2008 and April 2018 there were 53, 161 patients admitted with empyema. There was male predominance (67% vs 33%). The incidence of empyema has significantly increased from 4916 in 2008 to 7011 in 2017, see figure. There was seasonal variation with rates in the winter months increasing by a quarter. The median hospital length of stay in adults was 17 days (IQR 8 to 32). The proportion requiring surgery has remained stable (15.2%), but the proportion of open surgery has fallen. Mortality rates remain approximately 12–14% throughout the study period. Incidence correlates closely with rates of viral influenza (r=0.60) and was highest in the children and young adults during the 2010/2011 influenza season. Conclusion: This is the first population level assessment of empyema incidence in this country. Rates of empyema admissions have steadily increased with a seasonal variation that may be related to influenza incidence. Results of linkage of the HES data to Public Health England influenza statistics will be presented at the conference. References: Finley C, Clifton J, Fitzgerald JM, Yee J. Empyema: an increasing concern in Canada. Can Respir J . 2008;15(2):85–9. Farjah F, Symons RG, Krishnadasan B, Wood DE, Flum DR. Management of pleural space infections: a population-based analysis. J Thorac Cardiovasc Surg . 2007;133(2):346–51.